KONDUKTIVITAS TERMAL PASIR KALI SEBAGAI MEDIA PENGHANTAR PANAS PADA PROSES PENYANGRAIAN KERUPUK - Nirwana, Lina; Rais, Muhammad; Jamaluddin P, Jamaluddin P (Universitas Negeri Makassar, 2017)
The aims of this research was to determine the heat conductivity of river sand with different diameters as a heat transfer medium in the crackers roasting process. This research is experiment research using two types of sand diameter is big diameter sand and small diameter sand at three (3) temperature variations of 120, 140 and 160OC, and four (4) variations long of roasting is 10, 15, 20 and 25 seconds. During the roasting process do temperature measuremen on the sand and crackers, calculating the value of thermal conductivity of the sand and measurement of moisture content. The results showed that the smaller diameter of the sand cause heat transfer the faster so thermal conductivity value higher. The higher the temperature and the longer roasting process using small sand cause the heat transfer faster so the evaporation of water content in the crackers is greater. The higher the thermal conductivity value of the sand, so heat transfer is getting better.